2021
DOI: 10.21037/jtd-20-2349
|View full text |Cite
|
Sign up to set email alerts
|

Prompt surgery is effective for acute type A aortic dissection with cerebral ischemia

Abstract: Background: Acute type A aortic dissection (aTAAD) with preoperative cerebral ischemia (CI) is common and lethal, but the timing and treatment method remain uncertain. We retrospectively reviewed our aTAAD patients with CI and analyzed the outcomes and related risk factors. Methods: From January 2011 to December 2019, 1,173 patients diagnosed with aTAAD from Nanjing Drum Tower Hospital were enrolled. Among them, 131 patients had CI preoperatively (CI group), and 1,042 patients were in the non-CI group. One hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This discrepancy could be explained by the fact that prompt surgery was often performed for these patients in our center. Under such a policy, the prognosis of these patients following emergent surgery can be similar to those who did not present with malperfusion syndromes upon admission ( Xue et al, 2021 ). With recent advances of surgical techniques and equipment, the overall perioperative mortality and long‐term survival rate of ATAAD patients with organ malperfusion has been greatly improved.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy could be explained by the fact that prompt surgery was often performed for these patients in our center. Under such a policy, the prognosis of these patients following emergent surgery can be similar to those who did not present with malperfusion syndromes upon admission ( Xue et al, 2021 ). With recent advances of surgical techniques and equipment, the overall perioperative mortality and long‐term survival rate of ATAAD patients with organ malperfusion has been greatly improved.…”
Section: Discussionmentioning
confidence: 99%
“…Tsukube et al [ 32 ] suggested that surgery immediately after coma symptoms (within 5 h) is the preferred method of treating such patients. Xue et al [ 33 ] reported that immediate surgery is recommended for patients with transient coma. Overall, coma duration greater than 12.75 h is associated with a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…This has been supported by a recent report on patients presenting with cerebral ischemia, where surgical repair of aortic dissection within 12.5 h, was associated with favourable outcome. 19 Coronary malperfusion leading to ischemia requires an aortic root replacement in most instances or concomitant coronary artery bypass grafting and carries a significantly higher mortality. 20…”
Section: Discussionmentioning
confidence: 99%